The Effect of Content Marketing and Electronic Word of Mouth (eWOM) on the Development of MSMEs Coffee Ground Sunter in Moderation of Entrepreneurial Behavior - Kustiadi Basuki; Intan Endah RR (Budapest International Research and Critics University, 2022)
The purpose of this research is to locate entrepreneurial behavior as a moderating variable on the effect of content marketing and E-WOM on the development of MSMEs. The research population is to increase MSMEs in Indonesia. Data collection techniques by distributing questionnaires through google form. The results of the study show that content marketing, E-WOM and entrepreneurial behavior have a positive and significant effect on the development of MSMEs, the method of entrepreneurial behavior on the influence of content marketing has no effect on the development of MSMEs. Moderation of entrepreneurial behavior on the influence of E-WOM has no effect on the development of SMEs which are moderated by entrepreneurial behavior.